2005
DOI: 10.2460/javma.2005.226.767
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factors for the spread of low pathogenicity H7N2 avian influenza virus among commercial poultry farms

Abstract: Results suggest that an important factor contributing to rapid early spread of AI virus infection among commercial poultry farms during this outbreak was disposal of dead birds via rendering off-farm. Because of the highly infectious nature of AI virus and the devastating economic impact of outbreaks, poultry farmers should consider carcass disposal techniques that do not require off-farm movement, such as burial, composting, or incineration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 12 publications
5
74
1
Order By: Relevance
“…For all four epidemics, the following interventions were carried out by the Regional Veterinary Services in the areas involved in the epidemics : monitoring of flocks at risk of infection, stamping out or controlled marketing of all birds on IFs, ban or controlled restocking and movement restrictions for live birds, vehicles and staff [15,16].…”
Section: Control Measuresmentioning
confidence: 99%
“…For all four epidemics, the following interventions were carried out by the Regional Veterinary Services in the areas involved in the epidemics : monitoring of flocks at risk of infection, stamping out or controlled marketing of all birds on IFs, ban or controlled restocking and movement restrictions for live birds, vehicles and staff [15,16].…”
Section: Control Measuresmentioning
confidence: 99%
“…The differing levels of adoption by different household poultry producers have implications for the overall breach in biosecurity with the consequent risks of infection in the household. Low frequencies of adoption of a comprehensive biosecurity package have been confirmed in previous studies to contribute significantly to disease outbreaks on farms (Bos et al, 2007;East, 2007;Kung et al, 2007;McQuiston et al, 2005;Thomas et al, 2005;Dorea et al, 2010;Fasina et al, 2011The adoption of certain measures however indicated that given the right atmosphere, the household producers were willing to improve their management and disease control practices.…”
Section: Discussionmentioning
confidence: 76%
“…Poultry farmers should consider carcass disposal techniques that do not require off-farm movement, such as burial, composting and incineration, because of the highly infectious nature of AI virus and the devastating economic impact of outbreaks [3]. In an outbreak of HPAI, in-farm or near-farm disposal is basically required.…”
Section: Discussionmentioning
confidence: 99%